Ca3(BO3)2, a first wide waveband borate Raman laser crystal with strong Raman effects and outstanding anti-optical damage ability. Issue 41 (8th September 2015) - Liu, Yanqing; Zhang, Fang; Wang, Zhengping; Yu, Fapeng; Wei, Lei; Xu, Xinguang; Zhao, Xian
Abstract : Borate crystals Ca3 (BO3 )2 are realized for stimulated Raman scattering from deep ultraviolet to near infrared. Abstract : A borate crystal, Ca3 (BO3 )2, is reported for stimulated Raman scattering (SRS) from deep ultraviolet to near infrared. This crystal was found to possess a strong Raman response, and an outstanding anti-optical damage threshold as well as being easy to grow and having a low production cost. The short ultraviolet cut-off wavelength of 180 nm makes it available for deep ultraviolet or even vacuum ultraviolet SRS.